A new name for extant Potamogeton × mirabilis (Potamogetonaceae) - Kottaimuthu, Ramalingam; Kumar, John Kennedy John Praveen; Dineshkumar, Panjavarnam; Logeshwari, Maruthan (Phytotaxa, 2021)
The genus Potamogeton Linnaeus (1753: 126) is commonly called as pond weeds and they are the largest genera in the family Potamogetonaceae with about 88 species (POWO 2021). Furthermore the genus is noted for its high phenotypic plasticity and frequent hybridization that prompts impressive challenges in the delimitation and identification of species (Kaplan et al. 2009, 2013). A few instances of the homonymy among living and fossil monocots have been as of late settled by various workers (Turner 2014, Doweld 2016, 2018, Govaerts 2018, Kottaimuthu & Basu 2020). Recently we found that the extant hybrid Potamogeton × mirabilis Kaplan et al. (2009: 630) is an illegitimate later homonym according to Art.53.1. of ICN (Turland et al. 2018) because the name was already used by Kutuzkina (1957) to a fossil-species from Kyrgyzstan (formerly USSR). Hence a new replacement name is proposed for this nothospecies.